2017
DOI: 10.1111/cobi.12926
|View full text |Cite
|
Sign up to set email alerts
|

Estimating freshwater turtle mortality rates and population declines following hook ingestion

Abstract: Freshwater turtle populations are susceptible to declines following small increases in the mortality of adults, making it essential to identify and understand potential threats. Freshwater turtles ingest fish hooks associated with recreational angling, and this is likely a problem because hook ingestion is a source of additive mortality for sea turtles. We used a Bayesian-modeling framework, observed rates of hook ingestion by freshwater turtles, and mortality of sea turtles from hook ingestion to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Adult turtles are overharvested for both human consumption and the pet industry 11,12 , can experience high road mortality 13,14 , and are killed by human-introduced predators when they nest or disperse 10,15 . Turtles are struck by boats 16 , drowned in fishing nets and other human structures 17,18 , and wounded or killed by anglers 19,20 . Mortality of eggs and young has also increased, primarily because of poaching and predation by introduced predators 9,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Adult turtles are overharvested for both human consumption and the pet industry 11,12 , can experience high road mortality 13,14 , and are killed by human-introduced predators when they nest or disperse 10,15 . Turtles are struck by boats 16 , drowned in fishing nets and other human structures 17,18 , and wounded or killed by anglers 19,20 . Mortality of eggs and young has also increased, primarily because of poaching and predation by introduced predators 9,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems possible that incidental drowning on trot lines, limb lines, and submerged hoop nets (or even ingestion of fish hooks after being cut off a fishing line) could be a major source of contemporary mortality in southwestern Louisiana. Ultimately, this could threaten the long‐term population viability of alligator snapping turtles as a result of lowered annual adult survival rates (Folt et al , Steen and Robinson ).…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, Huntzinger et al () reported a dead alligator snapping turtle on a limb line, while several of our questionnaire responses also mentioned finding alligator snapping turtles dead on trot lines or in nets. Enge et al () found 12–36% of alligator snapping turtles radiographed in Florida, USA, contained ingested fish hooks, while Steen and Robinson () estimated that the mortality rates of alligator snapping turtles could be as high as 6% after ingesting fish hooks, leading to a 64% increase in the probability that a population will decline. Therefore, it seems possible that incidental drowning on trot lines, limb lines, and submerged hoop nets (or even ingestion of fish hooks after being cut off a fishing line) could be a major source of contemporary mortality in southwestern Louisiana.…”
Section: Discussionmentioning
confidence: 99%
“…The extirpation of Eastern Musk Turtle (Sterno therus odoratus) around the city of Hamilton, Ontario, is believed to have been the result of angling combined with habitat modification (Lamond 1994cited in COSEWIC 2012. Steen and Robinson (2017) dem onstrate that in settings where recreational fishing pressure is intense, hooking by anglers could have a great enough impact to affect populations. Steen et al (2014) x-rayed over 600 turtles from five rivers in the southeastern United States and found that the prevalence of ingested fish hooks ranged from 0% to 33% depending on species, sex, age class, and site; the highest rate, 33%, was for adult female Snapping…”
Section: Introductionmentioning
confidence: 99%